ESTABLISHMENT OF THE NATIONAL INNOVATION SYSTEM AND IMPROVEMENT OF APPROACHES TO REGULATING THE DEVELOPMENT OF INNOVATIVE ENTREPRENEURSHIP IN UKRAINE - Buła, Piotr; Putytskyi , Anton; Luzhna, Anastasiia (Socio-economic relations in the digital society, 2022)
The creation, financing, and use of higher-level technologies are of great importance in the economic growth of the national economy. Under these conditions, the task of forming and developing the national innovation system and solving the problem of increasing the regulation of the activities of domestic innovative business structures is of fundamental importance in Ukraine. The article substantiates that the lack of a balanced state policy restrains the process of developing a network of innovative infrastructures, and the low level of domestic investments and budget allocations for science, the current criteria for classifying business entities as innovative-type enterprises, non-designated applications, and the termination of benefits to innovative enterprises negatively affect the formation of the national innovation system of Ukraine. The regulation of the development of innovative enterprises is considered as a separate component of the general system of managing the innovative development of the economy, aimed at supporting its innovation-priority areas by creating an effective legislative framework and an appropriate financial and credit mechanism. The article formulates the principles of improving the organizational, economic and information support of the process of regulation of the national innovation system; the peculiarities of the separation and interconnection of the main elements in the scheme of the phased implementation of the system of regulating the development of innovative entrepreneurship in Ukraine are determined. A scheme for the phased implementation of the program of financial and credit regulation of the development of innovative entrepreneurship in Ukraine is proposed, as well as a scheme for improving the development of the national innovation system in the context of the implementation of the goals, objectives, and tasks of the innovative development of the Ukrainian economy.